PERLINDUNGAN DATA BIOMETRIK DALAM SEKTOR PERBANKAN DI INDONESIA DAN AMERIKA SERIKAT - Asokawati, Ainunnisa Rezky (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyze and compare the regulation and implementation of biometric data protection in the banking sector in Indonesia and the United States. In addition, this study also evaluates the security risks of biometric data and provides policy recommendations to improve its protection. This study uses a doctrinal method using primary and secondary legal sources. The focus of this study is to examine how the Indonesian State protects biometrics as personal data in a legal context and to compare the regulations and implementation related to biometrics in the banking sector in Indonesia and the United States. Based on the results of the study, in general, it was found that both have regulated the financial services sector, especially banking, and the technical management of personal data of customers and/or prospective customers. However, there are no detailed regulations aimed at protecting the biometrics of banking consumers. The absence of specific regulations on biometric data protection in the banking sector requires banks to take proactive steps in securing customer data, such as strengthening security systems and adopting strict internal policies. In addition, the government needs to consider creating more detailed regulations to provide legal certainty and better protection for consumers.